2010
DOI: 10.1111/j.1654-109x.2010.01081.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival and growth responses of eight Everglades tree species along an experimental hydrological gradient on two tree island types

Abstract: Questions: How are the early survival and growth of seedlings of Everglades tree species planted in an experimental setting on artificial tree islands affected by hydrology and substrate type? What are the implications of these responses for broader tree island restoration efforts? Location: Loxahatchee Impoundment Landscape Assessment (LILA), Boynton Beach, Florida, USA. Methods: An experiment was designed to test hydrological and substrate effects on seedling growth and survivorship. Two islands – a peat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…4). At the center of the limestone islands, peat was detected to an average depth of 11 cm, and was underlain by limestone rubble that extended to an average depth of 59 cm (Stoffella et al 2010). In all other areas on the limestone and peat islands, the peat extended from the surface to a depth of at least 60 cm.…”
Section: Lithologymentioning
confidence: 94%
See 1 more Smart Citation
“…4). At the center of the limestone islands, peat was detected to an average depth of 11 cm, and was underlain by limestone rubble that extended to an average depth of 59 cm (Stoffella et al 2010). In all other areas on the limestone and peat islands, the peat extended from the surface to a depth of at least 60 cm.…”
Section: Lithologymentioning
confidence: 94%
“…Stoffella et al (2010) found that the height of the trees increased on the peat tree islands with increasing elevation. Furthermore, they noted from aerial photos that fewer ruderal herbs and shrubs persisted in the center of the peat tree islands compared to the limestone.…”
Section: Biomassmentioning
confidence: 99%
“…Since flooding stress is one of the major factors that determine the survival and growth of plant species, differences in flood tolerance ability among species may easily be expressed (see Stoffella et al, 2010). A. glabra has been consistently ranked among the most flood tolerant Everglades tree island species, while C. icaco appears to be somewhat less flood tolerant (Armentano et al 2002;Gunderson et al 1988;Jones et al 2006;van der Valk et al 2007).…”
Section: Nutrient Availability and Substrate Effectmentioning
confidence: 99%
“…The M1E, M2W, M3W, and M4E islands were built around a limestone core, obtained from locally mined limestone, and were capped with ca. 0.3 m of peat (Stofella et al 2010). The limestone tree islands resemble the tree islands of the southern Everglades whereas M1W, M2E, M3E, and M4W were constructed using the same peat soil found in LILA to resemble the peat tree islands that predominate in the northern Everglades.…”
Section: Study Areamentioning
confidence: 99%
“…The limestone tree islands resemble the tree islands of the southern Everglades whereas M1W, M2E, M3E, and M4W were constructed using the same peat soil found in LILA to resemble the peat tree islands that predominate in the northern Everglades. The slopes of the central plateau of the tree islands were graded 16:1 along the north-south axis and 12:1 along the east-west axis (Stofella et al 2010). …”
Section: Study Areamentioning
confidence: 99%